Розробка інформаційної сисеми підтримки пошуку волонтерської допомоги - Тютюнник, А. С. (ХНУРЕ, 2023)
This work is devoted to the development of an electronic application system to provide the opportunity to perform volunteer work. A system for providing volunteer assistance online is being created, automating the process of submitting an ad for assistance and the response of volunteers to it. The server and client parts of the system for viewing information about announcements and response to applications have been developed. With the help of this system, anyone who wants to join the help can do so, and at the same time, those who want to receive help can receive it